THE CONTEMPORARY WORLD-SYSTEM: A CONTRIBUTION TO THE DEBATE ON DEVELOPMENT IN THE WORLD-SYSTEMS THEORY - Pereira, Analúcia Danilevicz; Xerri, Salvatore Gasparini (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
This work analyzes the development in World-System Theory as produced by the flow of appropriation of global surplus value through the international division of labor, creating the divisions between center, semiperiphery and periphery in the capitalist world-economy. It thus aims to explore how the global appropriation of surplus value in the capitalist world-economy produces variations in the level of development of its different regions. To this end, it contextualizes and conceptualizes its elements on its spatial and temporal dimensions. It defines surplus value and the form of its global accumulation, and in this sense explores the succession of capitalist hegemonies, in their dialectical relationship with the system’s progress, enabling the approach to the international division of labor, and how the monopoly over finance and technologies allows the center of the system to consolidate a structure that ensures the transfer of capital and surplus value from the other regions to it. It follows that the development of a particular country or region in the capitalist world-economy depends on its ability to accumulate surplus value globally. Additionally, it is observed that the conditions imposed by the system structure prevent initiatives of autonomous development by its parts, being necessary to break with them for such a project to be possible